Konsolidasi Demokrasi Melalui Liga Santri Nusantara - Indhar Wahyu Wira Harjo (Laboratorium Sosiologi Universitas Nahdlatul Ulama Indonesia Jakarta, 2020)
The present study investigates the relation between civil society organization (CSO) and government in dealing with the attempts to strengthen democratic practice. The aim of the study is to illustrate that CSO and government has collaborated in democratic consolidation through sports development. The study implemented qualitative research method with the approach of critical discourse analysis. The result of the study revealed that Liga Santri Nusantara (LSN – Indonesian Students’ League) was a type of sport trainings for potential students in Indonesia. In addition, the football competition was also a means for Rabithah Ma’ahid Islamiah Nahdlatul Ulama (RMI NU) and Nahdlatul Ulama (NU) to participate in democratic consolidation in Indonesia. LSN was a form of democratic consolidation in Indonesia that encompassed three key aspects. First, the consolidation took place on the aspect of participation in formulating the policy of how to manage the performance of LSN, the second was on the implementation of the policy, and the last was on the forming room for RMI NU’s and NU’s ideas. The democratic consolidation left some hurdles and challenges while there was a miscoordination and misadministration. The CSO participation in government’s development programs did not simply play a prominent role for the democratic consolidation. The participation that obeyed the regulations and authorities had a significant position that was way more important than any involvement that even weakened the practice of democracy in Indonesia.